Semi-active, active and non-delay schedules for the resource-constrained project scheduling problem - Arno Sprecher; Rainer Kolisch; Andreas Drexl (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1993)
We consider the resource-constrained project scheduling problem (RCPSP). The focus of the paper is on a formal definition of semi-active, active, and non-delay schedules. Traditionally these schedules establish basic concepts within the job shop scheduling literature. There they are usually defined in a rather informal way which does not create any substantial problems. Using these concepts in the more general RCPSP without giving a formal definition may cause serious problems. After providing a formal definition of semi-active, active, and non-delay schedules for the RCPSP we outline some of these problems occurring within the disjunctive arc concept.
Keywords: 650; Resource-constrained project scheduling; semi-active; active; and non-delay schedules; branch-and-bound methods; Projektmanagement; Theorie